A human-in-the-loop haptic interaction with subjective evaluation - Fang , Ying; Qiao , Yangjun; Zeng, Fanrong; Zhang, Keke; Zhao , Tiesong (Frontiers in Virtual Reality, 2022)
To date, one of the challenges in Human-Computer Interaction (HCI) is fully immersive multisensory remote physical interaction technologies. The applications of haptic perception in HCI can enrich the interaction details and effectively improve the immersion and realism of interaction. In the human-in-the-loop haptic interaction system, the quality of experience (QoE) of the human operator plays an essential role. However, QoE in haptic interaction is still in its infancy. Based on the typical application scenarios of haptic operation, the paper constructs a haptic-visual interaction framework and analyzes the QoE influencing factors. Through subjective evaluation experiments, the paper establishes a haptic interaction database which can provide a research basis for further exploring the relationship between various influencing factors and interactive QoE.